Harnessing the Power of Digital Collaboration: The Mediating Role of Knowledge Sharing in Enhancing Innovative Work Behaviour - Wulandari, Dian; Mubarok, Fakhri; Novita, Lina (JURNAL AL-TANZIM, 2025)
This study investigates the impact of Information and Communication Technology (ICT) utilization and digital collective synergy on the Innovative Work Behavior (IWB) of teachers in Islamic elementary schools (SDI). The study aims to fill the gap in understanding how knowledge sharing mediates the relationship between ICT utilization, digital collective synergy, and IWB. A quantitative approach was employed, using a structured survey distributed to 144 teachers selected through multistage cluster sampling. The data were analyzed using Structural Equation Modeling (SEM) to test the hypothesized relationships. The findings reveal that ICT utilization and knowledge sharing significantly contribute to enhancing IWB, while digital collective synergy does not have a direct impact. However, knowledge sharing proved to be a key mediator between ICT utilization and IWB. These results suggest that fostering a collaborative environment and encouraging knowledge sharing among teachers can enhance their innovative capabilities. The implications of this study highlight the importance of integrating ICT and knowledge-sharing initiatives in teacher development programs. This research contributes to the understanding of how technology and collaboration influence innovation in education, offering insights for policymakers and educational leaders to create more effective learning environments.